Black Holes are Rejuvenating Systems of the Universe - Sorli, Amrit Srecko (JOURNAL OF ADVANCES IN PHYSICS, 2020)
Recent research on superfluid quantum vacuum as the physical origin of universal space has opened new perspectives in astronomy and cosmology. Every stellar object is in the active relation with space and its density diminishes according to the mass-energy equivalence principle. As per Newton’s Shell Theorem, vacuum density is minimum at the surface of the stellar objects and in their centre. The density of space on the surface of the Black holes and in their centre is so low that atoms become unstable. Therefore, they disintegrate back into the elementary particles and cosmic rays. By transforming old matter into these fresh energies, black holes are rejuvenating the universe and keeping its entropy constant.